HUBUNGAN PENGETAHAUN IBU HAMIL DENGAN TINGKAT KECEMASAN MENJELANG PERSALINAN PADA MASA PANDEMI COVID-19 DI WILAYAH KERJA PUSKESMAS MANGUNJAYA DAN SUMBERJAYA KABUPATEN BEKASI - Mukaromah, Nahdiyatul; Raden, Abkar; Warsiti, Warsiti (Universitas Muhammadiyah Mataram, 2023)
Abstract: Globally, approximately 10% of pregnant women experience mental health disorders prior to the pandemic, with anxiety levels at 16%, which escalated to 57% during the COVID-19 pandemic. This increase in symptoms of depression and anxiety has been associated with a heightened risk of postpartum depression. Knowledge related to COVID-19 has been identified as a factor influencing anxiety among pregnant women. This study aims to examine the relationship between pregnant women's knowledge prior to delivery and their anxiety levels during the COVID-19 pandemic. The research employed an analytical survey design with a cross-sectional approach, utilizing both online and offline questionnaires for data collection. The sample was selected using accidental sampling, comprising 87 pregnant women. The findings indicate a significant relationship between knowledge and anxiety, with a p-value of 0.012 and an odds ratio (OR) of 4.880. Pregnant women with higher knowledge levels were 4.880 times more likely to experience reduced anxiety. These results suggest that increased knowledge among pregnant women is associated with lower anxiety levels, highlighting the importance of anxiety screening to enable monitoring and prevent anxiety during pregnancy.Abstrak: Secara global sekitar 10% ibu hamil menderita gangguan mental sebelum pandemi, dan tingkat kecemasan sebesar 16% dan meningkat menjadi 57% pada masa pandemi COVDI-19. Peningkatan gejala depresi dan kecemasan berhubungan dengan peningkatan depresi pasca melahirkan. Pengetahuan terkait COVID-19 merupakan faktor yang berpengaruh pada kecemasan ibu hamil. Penelitian ini bertujuan untuk mengetahui hubungan pengertahuan ibu hamil menjelang persalinan dengan kecemasan pada masa pandemi COVID-19. Jenis penelitian ini adalah survey analitik dengan pendekatan cross sectional, tehnik pengumpulan data secara online dan offline menggunakan kuesioner. Pengambilan sampel dalam penelitian ini menggunakan teknik accidental sampling yang berjumlah 87 ibu hamil. Terdapat hubungan antara pengetahuan dengan kecemasan dengan nilai p-value 0,012 dengan nilai OR sebsesar 4,880, ibu yang memiliki pengetahuan yang tinggi dapat menurunka kecemasan sebesar 4,880 kali. Hasil dari Penelitian ini menemukan semakin tinggi pengetahuan ibu semakin rendah kecemasan yang dirasakan, perlu adanya skrining kecemasan sehingga dapat dilakukan pemantauan dan mencegah terjadinya kecemasan pada ibu hamil.